Ultrasonographic features associated with the lumbosacral or lumbar 5–6 symphyses in 64 horses with lumbosacral‐sacroiliac joint region pain (2012–2018). (19th December 2019) - Boado, A.; Nagy, A.; Dyson, S.
Summary: The ultrasonographic appearance of the lumbosacral symphysis of horses with no history of hindlimb lameness or thoracolumbosacral pain has previously been documented. The aims of the study were to describe the signalment and clinical findings in horses with ultrasonographic lesions of the fifth and sixth lumbar (L) vertebrae and lumbosacral symphyses and to determine whether lesions of the L5‐6 symphysis are only seen in horses with congenital sacralisation or other abnormalities of the lumbosacral symphysis. Horses in Group 1 (n = 25) underwent poor performance investigation and improved in ridden performance after infiltration of mepivacaine around the sacroiliac joints. Horses in Group 2 (n = 39) presented for investigation of changes in thoracolumbosacral shape or poor performance but did not undergo anaesthesia of the sacroiliac joint regions. The median ages were 10 and 19 years respectively for Groups 1 and 2. Mares (53.1%) were over‐represented relative to the normal populations of the clinics. All horses had poor development of the thoracolumbar epaxial and pelvic muscles and prominence of the lumbar spinous processes and the tubera sacrale. Most horses (70%) had reduced range of movement of the thoracolumbosacral region. Ultrasonographic features included irregular vertebral end plates; heterogeneous echogenicity of the intervertebral disc ± ventral protrusion; and displacement of the ventral longitudinal ligament ± alteration in its echogenicity. In Group 1, abnormalities of the L5‐6 symphysis were seen in 13 horses, of which 84.6% had congenital sacralisation or narrowing of the lumbosacral symphysis. In Group 2, the majority of horses had lesions of both the L5‐6 and lumbosacral symphyses; only 9/39 horses (23.1%) had congenital fusion of either joint. Limitations include the lack of age‐matched control horses. However, the purpose of the study was to raise awareness of lesions of the L5‐6 and lumbosacral symphyses, which may contribute to pain and poor performance.